Efficacy of metronidazole to prevent active pulmonary tuberculosis in people living with HIV/AIDS on highly active anti-retroviral therapy: a prospective cohort study - Suryana, Ketut (International Journal of Research in Medical Sciences, 2020)
Background: People living with HIV/AIDS (PLWHA) were more susceptible of Active Pulmonary Tuberculosis (APT) than non-PLWHA. Whether Metronidazole Preventive Therapy (MPT) may prevent APT, remain unclear. The objective of the study was to investigate efficacy of MPT and other associated risk factors of APT among PLWHA on Highly Active Anti Retroviral Therapy (HAART). Methods: A prospective cohort study included 182 PLWHA on HAART and asymptomatic tuberculosis (TB), 62 received MPT (first group) and 120 PLWHA did not receive MPT (second group). APT were diagnosed among the first group (4 participants) and the second group (26 participants). Monthly visit to replenish pills and to confirm APT. Efficacy of MPT to prevent APT, socio-demography and laboratory, were analyzed using Chi-square with significancy p<0.05. Results: Of 112 participants (62.20%) were males, 70 (37.80%) females, mean age (year) 37.31±9.83. Four (2.20%) of participants (first group) and 26 (14.47%) (second group) were confirmed APT (p=0.003). In bivariate analysis, sex (p=0.020), alcohol consumption (p=0.000); smoking (p=0.000), CD4 cell counts (<70 cell/µl) (p=0.001), previous history of TB (p=0.000) were the significant factors associated with APT. Participants who received MPT had a significantly lower risk of APT than participants who did not receive MPT (p=0.003). Other factors; weight, Hb, WBC, neutrophil, lymphocyte, Neutrophil Lymphocyte Ratio (NLR) were not significantly associated with APT. Conclusions: We found, a significant protective effect of MPT, prevent APT. Other significant associated risk factors of APT were sex (male), smoking, alcohol consumption, previous TB history, lower CD4 counts.